Development of back‐junction back‐contact silicon solar cells based on industrial processes. (7th March 2017) - Lu, Guilin; Wang, Jianqiang; Qian, Zhengyi; Shen, Wenzhong
Abstract: We have presented simplified industrial processes to fabricate high performance back‐junction back‐contact (BJBC) silicon solar cells. Good optical surface structures (solar averaged reflectance 2.5%) and high implied open‐circuit voltage (0.695 V) have been realized in the BJBC cell precursors through wet chemical processing, co‐diffusion, P ion implantation and annealing oxidation, as well as laser patterning and plasma enhanced chemical vapour deposition passivation processes. We have achieved a certified high efficiency of close to 22% on BJBC silicon solar cells with the size of 4.04 cm 2 by using screen printing and co‐firing technologies. The manufacturing process flow further successfully yields efficiency of around 21% BJBC silicon solar cells with enlarged sizes of 6 × 6 cm 2 . The present work has demonstrated that the commercialization of low‐cost and high‐efficiency BJBC solar cells is possible because we have used processes compatible with existing production lines. Copyright © 2017 John Wiley & Sons, Ltd. Abstract : We have achieved a certified high efficiency of 22% back‐junction back‐contact (BJBC) silicon solar cells with the size of 4.04 cm 2 by conventional industrial processes of co‐diffusion, P ion implantation and annealing oxidation, laser patterning as well as screen printing and co‐firing technologies. The manufacturing process flow further successfully yields the maximum efficiency of around 21% BJBC silicon solar cells with enlarged sizes of 6 × 6 cm 2 . This work has demonstrated the simplified processes for the low‐cost and high‐efficiency BJBC silicon solar cell industrialization.